2013
DOI: 10.1136/bmjopen-2013-003391
|View full text |Cite
|
Sign up to set email alerts
|

Modelling factors in primary care quality improvement: a cross-sectional study of premature CHD mortality

Abstract: ObjectivesTo identify features of primary care quality improvement associated with improved health outcomes using premature coronary heart disease (CHD) mortality as an example, and to determine impacts of different modelling approaches.DesignCross-sectional study of mortality rates in 229 general practices.SettingGeneral practices from three East Midlands primary care trusts.ParticipantsPatients registered to the practices above between April 2006 and March 2009.Main outcome measuresNumbers of CHD deaths in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
4
17
1
Order By: Relevance
“…These findings are in harmony with previous findings on association between GMP level premature mortality and socioeconomic status [21][22][23] and urban setting [24].…”
Section: Observations In International Contextsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in harmony with previous findings on association between GMP level premature mortality and socioeconomic status [21][22][23] and urban setting [24].…”
Section: Observations In International Contextsupporting
confidence: 91%
“…Our results, demonstrated that temporary GPs providing care in a vacant GMP have restricted effectiveness in managing patients compared to the effectiveness achieved by a permanent GP in Hungary, are in concordance with the demonstrated risky nature of the lack of continuity in PHC [22,23,[28][29][30].…”
Section: Observations In International Contextsupporting
confidence: 80%
“…However, sensitivity analysis including age variables did not impact on the size of effect of deprivation as an explanatory variable or size of the effect. Although negative binomial regression of counts of deaths would be preferred, 27 the data available meant that this approach was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Counts of deaths were not available, and it was not possible to use a count model. 27 Primary care trusts and mortality estimates, based on local areas that overlap for some general practices, cannot be considered independent. We adjusted for the clustering effect by using robust SEs.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies from the United Kingdom also suggest the association between continuity of care and reduced mortality, but they were limited by inconsistent results and the cross-sectional nature of one study. 30,31 We aimed to determine the impact of continuity of care on survival and health care costs in patients with newly diagnosed cardiovascular risk factors, since these represent important, preventable chronic conditions 32,33 to which continuity of care is likely to be highly relevant. 11,15,[34][35][36][37] In South Korea, virtually all Koreans (97%) are covered by National Health Insurance (KNHI), and may consult any primary care physician.…”
Section: Introductionmentioning
confidence: 99%